Biotechnological objects: philosophical conceptions and consequences for their evaluation - Olivé, León (Acta Bioethica, 2003)
Due to their intrinsic nature, biotechnological systems produce both benefits as well as risks and situations of uncertainty and ignorance. The evaluations of biotechnological systems, of the artifacts produced by them and of their consequences for society and the environment, depend both on intrinsic values of those systems as well as on values extrinsic to them, which in turn vary from one social group to another and which can hardly coincide completely. Such axiological plurality must be taken into account in reviewing biotechnology, for example about biosafety issues by experts from different social sectors (state agents, managers, non governmental organizations, advocacy groups) Therefore, mechanisms of participation of experts from different natural, social and humanistic disciplines must be established, along with non experts representing the social sectors with interests. These will watch over the impact of biotechnological systems and their artifacts, they will be able to take decisions and carry out actions to prevent, mitigate or counteract the negative consequences of biotechnology.